Ispaat Parivahan Limited : additional fleet acquisition - Raghuram, G.; Chakraborty, Souhardhya (London : Indian Institute of Management, Ahmedabad, 2015)
This case focuses on the issue of additional fleet acquisition by Ispaat Parivahan Limited (IPL) for its contract obligation fulfilment with Solid Steel Limited. As per contract, IPL was to transport overall 15,000 tons per month (tpm) till July 31, 2015 to the North and West. But IPL failed to uphold its part of the contract and fell short of the target for the North. IPL could transport only 12,800 tpm, leading to a penalty payment. To avoid this, the company proposed acquisition of more fleet. One of the issues was additional time due to return loads. The Board wanted IPL to assess scenarios with and without return loads.
Originally Published InRaghuram, G. & Chakraborty, S.(2015). Ispaat Parivahan Limited: Additional fleet acquisition. Ahmedabad, IN: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Ispaat Parivahan Limited; Trucking -- India -- Case studies; Small business -- India -- Case studies